From German prisoner of war to American citizen : a social history with 35 interviews - Heisler, Barbara Schmitter (Jefferson, North Carolina : McFarland & Company, Inc., Publishers, 2013)
" Drawing on archival sources and in-depth interviews with 35 former prisoners who immigrated, the book outlines the conditions and circumstances that defined their unusual experiences and traces their journeys from captive enemies to American citizens"--
The Germans are coming -- An astonishing introduction: thirty-five POWs experience America -- Repatriation to Germany and return to America -- Pathways to immigration: from German prisoner of war to American citizen -- Prisoners of war and international migration.
Includes bibliographical references and index.
Keywords: World War, 1939-1945 -- Prisoners and prisons, American; Prisoners of war -- United States -- Interviews; Prisoners of war -- Germany -- Interviews; Germans -- United States; Immigrants -- United States -- Interviews